Urgensi Rencana Kegiatan Ekstrakurikuler (RKE) Pada Pelaksanaan Kegiatan Ekstrakurikuler di Sekolah Dasar - Febby Nur Adhari; Neng Ani; Ridla ‘Adawiyyah (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
Problems in the world of education that occur, such as the decline in children's character, can damage the nation's generation. To overcome this, schools can find a solution by holding learning activities that can improve students' quality of life through character building. Character formation can be done with extracurricular activities. However, to carry out extracurricular programs you need a good plan, so that the vision and mission goals can be achieved according to plan. This research uses a qualitative method with a descriptive approach through literature studies regarding extracurricular activity plans. The aim of this research is to provide an understanding of the importance of planning extracurricular activities before carrying out the program so that extracurricular activities can run in a systematic and directed manner.